Bilingual advantages in executive functioning: Evidence from a low-income sample. Issue 6 (December 2021) - Grote, Kandice S.; Scott, Rose M.; Gilger, Jeffrey
Recent research suggests that bilinguals might exhibit advantages in several areas of executive function, including working memory, inhibitory control, and attentional control. However, few studies have examined potential bilingual advantages within lower socioeconomic status (SES) populations. Here we addressed this gap in the literature by investigating whether low-SES Spanish–English bilingual preschoolers exhibited advantages in executive function relative to two monolingual control groups (English, Spanish). Across three experiments, bilingual children exhibited superior performance on two different measures of visual–spatial memory, as well as measures of inhibitory and attentional control. These results suggest that bilinguals exhibit broad advantages in executive function during the preschool years, and these advantages are evident within a disadvantaged, low-SES population.